Bukti Baru Infeksi Natural Wolbachia sp. pada Aedes aegypti dengan Aedes albopictus dari Makassar - Fadly Rian Saputra; Isra Wahid; Rizalinda Sjahril; Din Syafruddin; Syahribulan Rani; Burhanuddin Bahar (Balai Penelitian dan Pengembangan Kesehatan Donggala, Badan Penelitian dan Pengembangan Kesehatan, Kementerian Kesehatan RI, 2020)
Abstract There is currently no research on the presence or absence of Wolbachia bacteria naturally in Ae. aegypti and Ae. albopictus mosquitoes in Makassar City. Therefore, it is necessary to study